2020
DOI: 10.1136/bmjopen-2020-040965
|View full text |Cite
|
Sign up to set email alerts
|

What is the risk of prostate cancer mortality following negative systematic TRUS-guided biopsies? A systematic review

Abstract: ObjectiveTo investigate the risk of prostate cancer-specific mortality (PCSM) following initial negative systematic transrectal ultrasound-guided (TRUS) prostate biopsies.DesignSystematic review.Data sourcesPubMed and Embase were searched using a string combination with keywords/Medical Subject Headings terms and free text in the search builder. Date of search was 13 April 2020.Study selectionStudies addressing PCSM following initial negative TRUS biopsies. Randomised controlled trials and population-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our data show that the risk of prostate cancer–specific death is almost identical to the risk of prostate cancer–specific death in men with benign systematic TRUS biopsies. A recent review reported that the risk of prostate cancer–specific death after benign TRUS biopsies ranged from 0.5% to 5.2% after 10–20 years of follow‐up, and there was a strong association with PSA 18,19 . The current study shows that the cumulative incidence of prostate cancer mortality was up to 0.8% after 15 years in men with PSA levels <10 ng/ml; this was an even lower incidence than the incidence of 1.3% after a benign initial biopsy 20,21 .…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Our data show that the risk of prostate cancer–specific death is almost identical to the risk of prostate cancer–specific death in men with benign systematic TRUS biopsies. A recent review reported that the risk of prostate cancer–specific death after benign TRUS biopsies ranged from 0.5% to 5.2% after 10–20 years of follow‐up, and there was a strong association with PSA 18,19 . The current study shows that the cumulative incidence of prostate cancer mortality was up to 0.8% after 15 years in men with PSA levels <10 ng/ml; this was an even lower incidence than the incidence of 1.3% after a benign initial biopsy 20,21 .…”
Section: Discussionmentioning
confidence: 43%
“…A recent review reported that the risk of prostate cancer-specific death after benign TRUS biopsies ranged from 0.5% to 5.2% after 10-20 years of follow-up, and there was a strong association with PSA. 18,19 The current study shows that the cumulative incidence of prostate cancer mortality was up to 0.8% after 15 years in men with PSA levels <10 ng/ml; this was an even lower incidence than the incidence of 1.3% after a benign initial biopsy. 20,21 This difference may be explained by the selection of patients for TURP; specifically, patients who undergo TURP have lower PSA levels than men with a negative first biopsy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…There have been distressing clinical cases where the window of opportunity for cure was missed when an initial biopsy failed to detect an aggressive cancer. However, population-based data demonstrate that these cases are rare and that the first TRUS biopsy can separate patients into two very different prognostic groups based on whether the biopsy is malignant or non-malignant [1,2]. Patients with initial non-malignant TRUS biopsies have a very low risk of prostate cancer-specific mortality in the absence of other 'red flags', such as a high PSA level.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thus, it is important to understand which patients with negative TRUS biopsy are at high risk of a missed lethal prostate cancer and, moreover, determine how TRUS re-biopsy performs in a population-based setting. 7–9 Here we build on our previously published result, including additional analysis of men with re-biopsies and extended followup. 8 We are particularly interested in mortality at 10–15 years as it seems unlikely, even given the prolonged lead time of prostate cancer, that failing to identify a cancer on TRUS biopsy would mean a missed opportunity for cure if mortality occurred more than 10–15 years subsequently.…”
mentioning
confidence: 99%